Mental health selection: common mental disorder and migration between multiple states of deprivation in a UK cohort - Greene, Giles (BMJ Open, 2020)
OBJECTIVES: To assess whether the direction of movement along the social gradient was associated with changes in mental health status. DESIGN: Longitudinal record-linkage study using a multistate model. SETTING: Caerphilly, Wales, UK between 2001 and 2015. PARTICIPANTS: The analytical sample included 10 892 (60.8% female) individuals aged 18–74 years. PRIMARY AND SECONDARY OUTCOME MEASURES: Deprivation change at lower super output area level using the 2008 Welsh Index of Multiple Deprivation. Mental health was assessed in 2001 and 2008 using the Mental Health Inventory subscale of the short-form 36 V.2. RESULTS: Mental health selection was shown whereby individuals with common mental health disorders were less likely to move to areas of lower deprivation but more likely to move to areas of greater deprivation. CONCLUSION: Poor mental health seems to drive health selection in a similar way to poor physical health. Therefore, funding targeted at areas of higher deprivation should consider the demand to be potentially higher as individuals with poor mental health may migrate into that area.